Manufacturing productivity, deindustrialization, and reindustrialization - Fiona Tregenna (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2011)
In considering pathways to industrialization in the twenty-first century, cognisance needs to be taken of the fact that many countries have actually been deindustrializing. This paper analyses deindustrialization experiences internationally, by decomposing changes in the level and share of manufacturing employment. The results indicate that in most countries the decline in manufacturing employment is associated mainly with rising labour productivity in manufacturing. Reindustrialization is likely to be important for long-term economic growth, yet it is difficult and is not common. This highlights the importance of robust industrial policies if countries are to move from deindustrialization to reindustrialization.
Keywords: E23; E24; J21; L16; L52; L60; O14; 330; deindustrialization; reindustrialization; manufacturing; employment; Industrialisierung; Deindustrialisierung; Verarbeitendes Gewerbe; Produktivität; Industrielle Beschäftigung